More than a game: An activity theory analysis of EFL learners’ Duolingo-mediated vocabulary learning practices - Alvan Rafiqi Al-firdausi; Ana Maghfiroh; Elok Putri Nimasari; Diyah Atiek Mustikawati (Englisia: Journal of Language, Education, and Humanities, 2026)
Numerous studies examining Duolingo within English as a Foreign Language (EFL) contexts have primarily focused on learning outcomes and user satisfaction, yet they seldom elucidate how vocabulary acquisition is systematically organized and sustained in learners’ daily routines. This gap is critical, as app-based language learning typically unfolds outside formal instructional environments. Guided by Activity Theory, this qualitative study conceptualizes Duolingo-mediated vocabulary learning as a dynamic activity system. Data were collected via an open-ended questionnaire administered to ten EFL learners recruited from an online language learning community, complemented by the researcher’s autoethnographic notes to enrich contextual understanding. Findings reveal that learners consistently engage in short, micro-sessions shaped by the platform’s segmented lesson structure. Sustained participation is enabled through self-imposed daily routines and the motivational affordance of socially visible progress indicators. Furthermore, learners actively negotiate contradictions-such as the tension between repetitive drills and meaningful use-by adjusting learning intensity or expanding their toolset to include external resources like personal notes and authentic media. These insights extend beyond descriptive accounts to inform more learning-centered design principles and pedagogical scaffolding strategies, ultimately fostering durable vocabulary development in technology-mediated, self-directed EFL environments.